(3LhGgQ GdcdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s
(3ChdgG (B:s
(3GdebOeI GdNGeSI aj ecGf GdeUdj, hbO bjd aj YQa GdabgGA Hjf eYfjjf CMOgeG HGYJHGQ EHGMJg(B...s
(3BNQgG (B:s
...(3hbO TGY aj ReGffG GdCPGf hGdEbGeI Nda GdeSGaQ MJi GSJYedg YdeGA GdYUQ aYkdG(B...s
(3fSNI efShNI hebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B92s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B378s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis